Joy and Guilt, Passion and Anxiety. Exploring Emotions in the Neoliberal Academia - Camilla Gaiaschi; Rossella Ghigi; Valeria Quaglia (Sociologica)
In this introduction to the Symposium on Emotions in Academic Work, we explore key reflections on emotion work, emotional labour, and feeling rules within contemporary academia, in light of the transformations brought about by the neoliberal reconfiguration of academic labour. Topics such as academic guilt, stress, time management, as well as joy and satisfaction, are examined through a gendered and intersectional lens.